Joint Space Width and Osteoarthritis in Patients Undergoing Hip Arthroscopy - Pidgeon, Tyler S.; Schiller, Jonathan R.; Gil, Joseph A.; Evangelista, Peter T.; Machan, Jason T.; Tabaddor, Ramin R. (The Journal of Hip Surgery, 2017)
Preoperative hip joint space width (JSW) of ≤2 mm on plain radiography has been shown to be predictive of intraoperative findings of osteoarthritis, worse functional outcomes, and failure to total hip arthroplasty following hip arthroscopy. However, there is no evidence to suggest that hip joint space greater than 2 mm can definitively rule out the presence of osteoarthritis. We hypothesize that a preoperative JSW of 2 mm or greater does not reliably rule out the presence of high-grade arthritis on hip arthroscopy. Retrospective review of 50 patients who underwent hip arthroscopy between January 11, 2010, and January 3, 2015, at a single institution was performed. Preoperative, standing anteroposterior hip radiographs were reviewed to determine the minimum hip JSW of each operative hip. Operative notes and images were reviewed to determine the Outerbridge classification of cartilage changes on both the acetabulum and femoral head for each patient. High-grade arthritis was defined as a minimum of grade 3 changes on either the femoral head or the acetabulum, which was required for inclusion in the study. The sensitivity of a JSW of 2 mm or less on preoperative radiographs to diagnose a patient with grade 3, grade 4, and grade 3 or 4 arthritis was calculated. Linear regression was used to test for an association between Outerbridge grading and the radiographic minimum JSW. The mean JSW for all patients was 3.5 ± 1.2 mm (range: 0–5.5 mm). Regression found an inverse relationship between joint space and the arthroscopic grading of the articular surfaces (p = 0.0031). However, a preoperative JSW of ≤ 2 mm was only 14.3% sensitive (95% confidence interval [CI] 2.6–51.3%) for predicting Outerbridge grade 3 changes, 7.3% sensitive (95% CI: 2.5–19.4%) for predicting Outerbridge grade 4 changes, and 8.3% sensitive (95% CI: 3.3–20.6%) for predicting Outerbridge grade 3 or 4 changes. The threshold of ≤2 mm of hip JSW on plain radiographs has poor sensitivity for predicting the existence of high-grade arthritis.
Keywords: hip arthroscopy; radiology; joint space width; osteoarthritis